Psychological qualities of elite adolescent rugby players: Parents, coaches, and sport administration staff perceptions and supporting roles - Woodcock, C.; Holland, M. J. G.; Duda, J. L.; Cumming, J. (The Sport Psychologist, 2011)
The aim of the current study was to extend previous research by Holland and colleagues (2010) into the required psychological qualities of young talented rugby players by considering the perceptions and supportive role of influential others. Perceptions of players` parents (n = 17), coaches (n = 7), and sport administration staff (SAS; n = 2) were explored through focus group discussions. Findings show that these influential others considered the same 11 higher order themes for psychological qualities previously identified as desirable by players. Their views on how they assisted in developing these player psychological qualities were classified into three higher-order themes, namely progressive development, professional environment, and performance environment. Specific behaviors contributing to each context and deemed helpful by influential others were discussed in terms of ecological systems theory (Bonfenbrenner, 1977). Recommendations for future research and applied implications for consultants are subsequently offered.